(untitled) (Web of Teachers: Inderscience Research, 2025)
By the concept of information and Communication Technology (ICT), we understand the combination of methods, tools and techniques for searching, storing, processing, presenting and transmitting graphic, text, digital, audio and video data based on personal computers, computer networks and communications.